The conduction velocity-potassium relationship in the heart is modulated by sodium and calcium - King, D. Ryan (Pflugers Arch, 2021)
The relationship between cardiac conduction velocity (CV) and extracellular potassium (K(+)) is biphasic, with modest hyperkalemia increasing CV and severe hyperkalemia slowing CV. Recent studies from our group suggest that elevating extracellular sodium (Na(+)) and calcium (Ca(2+)) can enhance CV by an extracellular pathway parallel to gap junctional coupling (GJC) called ephaptic coupling that can occur in the gap junction adjacent perinexus. However, it remains unknown whether these same interventions modulate CV as a function of K(+). We hypothesize that Na(+), Ca(2+), and GJC can attenuate conduction slowing consequent to severe hyperkalemia. Elevating Ca(2+) from 1.25 to 2.00 mM significantly narrowed perinexal width measured by transmission electron microscopy. Optically mapped, Langendorff-perfused guinea pig hearts perfused with increasing K(+) revealed the expected biphasic CV-K(+) relationship during perfusion with different Na(+) and Ca(2+) concentrations. Neither elevating Na(+) nor Ca(2+) alone consistently modulated the positive slope of CV-K(+) or conduction slowing at 10-mM K(+); however, combined Na(+) and Ca(2+) elevation significantly mitigated conduction slowing at 10-mM K(+). Pharmacologic GJC inhibition with 30-μM carbenoxolone slowed CV without changing the shape of CV-K(+) curves. A computational model of CV predicted that elevating Na(+) and narrowing clefts between myocytes, as occur with perinexal narrowing, reduces the positive and negative slopes of the CV-K(+) relationship but do not support a primary role of GJC or sodium channel conductance. These data demonstrate that combinatorial effects of Na(+) and Ca(2+) differentially modulate conduction during hyperkalemia, and enhancing determinants of ephaptic coupling may attenuate conduction changes in a variety of physiologic conditions. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s00424-021-02537-y.